Elite language personality in the syntactic representation of the diary discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article concerns some notification of the language personality formed in the frames of the diary discourse, there were also systemized its linguistic parameters and pointed out perspectives of the syntaxes modeling. The build up model is stressed with its inner communicative-pragmatic potential of the syntax construction and its necessity. In the constructed model is highlighted internal communicative-pragmatic potential syntactic structure is determined by its importance in the formation of the diary text. Infosegmenty revealed that significantly expand the boundaries of the diary of the information field.
Keywords: elite linguistic personality; syntax modeling; communicative and pragmatic potential; discourse